Current smoking and secondhand smoke exposure and depression among Korean adolescents: analysis of a national cross-sectional survey. Issue 2 (6th February 2014) - Lee, Kyung-Jae
Abstract : Objectives: To examine the association between cigarette smoke exposure and depression among Korean adolescents using the seventh Korea Youth Risk Behavior Web-based Survey (KYRBWS). Design: Cross-sectional study. Setting: A nationally representative sample of middle and high school students across South Korea. Participants: 75 643 eligible participants across the country. Primary outcome measures: Current smoking, secondhand smoke exposure and depression. Methodology: Data were analysed from a nationally representative survey of 75 643 participants (37 873 men and 37 770 women). Data were gathered on extensive information including current smoking, secondhand smoke exposure and depression in adolescence. Multiple logistic regression analysis was used to estimate the association between current smoking, secondhand smoke exposure and depression in Korean adolescents. Results: Among those who had never smoked, secondhand smoke exposure was positively associated with depression in male and female adolescents in a dose–response relation (OR 1.27, OR 1.52 in males; OR 1.25, OR 1.72 in females). Similar associations were observed among currently smoking men and women in a dose–response manner (OR 1.29, OR 1.55 in males; OR 1.22, OR 1.41 in females). These significant trends were consistently observed even after adjustments. Conclusions: We suggested that current smoking and secondhand smoke exposure were positively associated with depression in male and female adolescents. Efforts to encourage no smoking and no secondhand smoke exposure will be established for adolescents.